2020
DOI: 10.1108/lhtn-11-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Big data adoption in academic libraries: a literature review

Abstract: Purpose The purpose of this paper is to analyse the publication of big data in the library from Scopus database by looking at the writing time period of the papers, author's country, the most frequently occurring keywords, the article theme, the journal publisher and the group of keywords in the big data article. The methodology used in this study is a quantitative approach by extracting data from Scopus database publications with the keywords “big data” and “library” in May 2019. The collected data was analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The study also observed that big data and AI have been widely studied in the LIS discipline. This study concurs with the findings from prior literature (Ahmed and Ameen, 2017; Anna and Mannan, 2020) that addressed the emerging topics of big data and AI related research in LIS. In this way, influential terms extracted from this study describe the interdisciplinary points where the two academic fields would potentially be related to each other.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study also observed that big data and AI have been widely studied in the LIS discipline. This study concurs with the findings from prior literature (Ahmed and Ameen, 2017; Anna and Mannan, 2020) that addressed the emerging topics of big data and AI related research in LIS. In this way, influential terms extracted from this study describe the interdisciplinary points where the two academic fields would potentially be related to each other.…”
Section: Discussionsupporting
confidence: 91%
“…According to them, AI techniques can be applied to various areas in LIS, such as cataloging, indexing, information retrieval, reference and others. Anna and Mannan (2020) conducted a systematic literature review to explore big data analytics and data mining related research in LIS. They identified multiple clusters of relevant keywords, including “big data”, “libraries”, “library”, “data handling”, “data mining”, “university libraries”, “digital libraries”, “academic libraries”, “big data applications,” and “data management”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Big data flow within organisations is in an unprecedented way and need extensive processing (Halaweh and Massry, 2015). The rapid flow of information from all over the world has generated volumes of data that did not exist before (Anna and Mannan, 2020). Velocity refers to the speed of data processing and analysis (Ghasemaghaei, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Now libraries are coming into the user space, where they spend much of their time via social media applications and encourage their participation in resource management ( Yesmin and Ahmed, 2022; Mensah and Onyancha, 2021). Every year, academic libraries, in particular, have witnessed that the emerging technologies are more deeply embedded in their service components to facilitate user involvement (De Sarkar, 2017; Coghill, 2018; Anna and Mannan, 2020; Nitecki and Alter, 2021; Okunlaya et al , 2022).…”
Section: Introductionmentioning
confidence: 99%